Allelic variation at innate immune genes (avian β‐defensins), within a natural population of great tits. (15th October 2014) - Hellgren, Olof
<x xml:space="preserve">Abstract</x> In order to fully understand pathogen induced natural variation in fitness in wild animal populations it is important to identify and study the degree of non‐synonymous alleles in genes that code for components of the immune system. This study investigates the degree of natural genetic variation at 6 innate immune genes belonging to the β‐defensin family within a single population of birds, the great tits Parus major. In 40 adult individuals, all belonging to the same local population in Wytham Woods, Oxford, UK, screened across 6 different β‐defensin genes, all but one individual showed non‐synonymous heterozygosity within the exon coding for the mature defensin peptide. The non‐synonomous variation was thus associated with the part of the defensin gene that directly interacts with potential pathogens. Within the sample, 31 different genotypes were identified across the 6 different loci. Much of the found allelic variation affected the amino acid composition, which in turn alter the net charge and hydrophilicity of the produced peptide; properties associated with the efficiency of binding to and rupture pathogens. This study demonstrates that non‐synonymous genetic variation exists at β‐defensins genes, a part of the immune system that forms an important first line of defence against various pathogens. Understanding the degree of underlying genetic variation at different parts of the immune system will help achieve a holistic view of the reasons behind individual variation in pathogen susceptibility, as well as why individuals are affected differently once they become infected.